Aplikasi E-Piket Pada Kantor Desa Berbasis Web - Fahmi Kurniawan; Randi Rian Putra; Dwi Saraswati (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2023)
Information technology is growing from time to time, more and more corporate agencies, both government and one, apply information technology in carrying out their work. By using this information technology can facilitate a job that used to use a manual system has switched to a computerized system. This study aims to build an E-Picket application that will be applied at the Pertumbukan Village office, Wampu District, Langkat Regency. The benefits of this research can provide convenience for the Pertumbukan Village Office, Wampu District in making employee picket schedules in serving the needs of the community using a computerized system. Based on trials conducted, this e-picket application shows an increase in the performance of village office employees in serving the needs of the village community by scheduling employee pickets properly and supporting Pertumbukan village to make one of the villages that improve facilities and infrastructure in processing digitization-based picket data, namely using information system technology using electronic computer devices.